Impact of Personality Traits on Knowledge Hiding: A Comparative Study on Technology-Based Online and Physical Education - Wu, Jian (Frontiers in Psychology, 2021)
Knowledge hiding has been a variable of interest that has led major intangible losses to the organizations. Especially in this era of pandemic when everything has shifted to the online platforms and social media, knowledge hiding has taken a new turn into the field of knowledge management. Moreover, the major player in knowledge hiding has been found to be the personality characteristics of individuals that has now found a way out without coming into the highlight. This study has also been one of the studies needed in this time of online working environment where the role of personality traits and psychological ownership has been explored in order to understand their impact on the knowledge hiding in organizations of China. Furthermore, to understand what role does social status play in moderating these relationships. The sampling design used is the convenient random sampling with a sample size of 298 of the managers. This study has used the software Smart PLS 3.3.3 for analyzing the data. The data had been relied and validated using preliminary tests of reliability and discriminant and convergent validities using the measurement model algorithm. Further, partial least square technique was used to find the equation modeling for the variables; with the help of structural model algorithm using 500 iterations for bootstrapping. Findings of the current study show that personality traits of big five model positively predict the knowledge hiding however except for openness to experience while psychological ownership plays a partial mediating role.